Assessing thermal adaptation using family‐based association and FST outlier tests in a threatened trout species. Issue 10 (11th May 2019) - Amish, Stephen J.; Ali, Omar; Peacock, Mary; Miller, Michael; Robinson, Morgan; Smith, Seth; Luikart, Gordon; Neville, Helen
Abstract: Discovering genetic markers associated with phenotypic or ecological characteristics can improve our understanding of adaptation and guide conservation of key evolutionary traits. The Lahontan cutthroat trout ( Oncorhynchus clarkii henshawi ) of the northern Great Basin Desert, USA, demonstrated exceptional tolerance to high temperatures in the desert lakes where it resided historically. This trait is central to a conservation hatchery effort to protect the genetic legacy of the nearly extinct lake ecotype. We genotyped full‐sibling families from this conservation broodstock and samples from the only two remaining, thermally distinct, native lake populations at 4, 644 new single nucleotide polymorphisms (SNPs). Family‐based genome‐wide association testing of the broodstock identified nine and 26 SNPs associated with thermal tolerance ( p < 0.05 and p < 0.1), measured in a previous thermal challenge experiment. Genes near the associated SNPs had complex functions related to immunity, growth, metabolism and ion homeostasis. Principal component analysis using the thermotolerance‐related SNPs showed unexpected divergence between the conservation broodstock and the native lake populations at these loci. F ST outlier tests on the native lake populations identified 18 loci shared between two or more of the tests, with two SNPs identified by all three tests ( p < 0.01); none overlapped with loci identified by association testing in the broodstock. A recent history of isolation and the complex genetic and demographic backgrounds of Lahontan cutthroat trout probably limited our ability to find shared thermal tolerance loci. Our study extends the still relatively rare application of genomic tools testing for markers associated with important phenotypic or environmental characteristics in species of conservation concern.